Penerapan Model Pembelajaran Kooperatif Jigsaw Tipe I untuk Meningkatkan Penguasaan Materi Gerak dan Gaya - Siwalette, Loura Angela; Huliselan, Estevanus Kristian; Nirahua, Juliana (Pattimura University, 2024)
The goal of this study is to find out if the Jigsaw type I cooperative learning model helps grade VIII students at SMP Negeri 4 Kairatu learn more about motion and force. We classify this research as a descriptive quantitative type, with the aim of presenting an accurate picture or scenario of the mastery profile of physics material. This study employed a one-group pre-test and post-test research design. This study utilized grade VIII as its sample, comprising a total of 21 students. Researchers collected data for this study using both test and non-test instruments. Researchers utilized test instruments for both the initial and final tests. This instrument includes 15 multiple-choice questions and 10 description questions, in addition to non-tests in the form of student worksheets (LKPD), which are designed to evaluate cognitive aspects of learning. The initial test results revealed that 100% of students failed, with an average achievement score of 43.29. The maximum achievement score was 57.14, while the minimum was 28.57. The analysis of material mastery during the Jigsaw type I learning process reveals that the average achievement score of students is 89.52, indicating a good qualification. After learning, students' abilities demonstrate a significant change. The average score for students' material mastery achievement was 86.70, indicating a good qualification level. The N-Gain test results yielded a score of 0.75, positioning the students in the high category. Therefore, grade VIII students at SMP Negeri 4 Kairatu can enhance their understanding of motion and force material by implementing the Jigsaw type I cooperative learning model.